Mapping Epitopes of the Plasmodium vivax Duffy Binding Protein with Naturally Acquired Inhibitory Antibodies - Chootong, Patchanee (American Society for Microbiology (ASM), 2010)
Plasmodium vivax Duffy binding protein (DBP) is a merozoite microneme ligand vital for blood-stage infection, which makes it an important candidate vaccine for antibody-mediated immunity against vivax malaria. A differential screen with a linear peptide array compared the reactivities of noninhibitory and inhibitory high-titer human immune sera to identify target epitopes associated with protective immunity. Naturally acquired anti-DBP-specific serologic responses observed in the residents of a region of Papua New Guinea where P. vivax is highly endemic exhibited significant changes in DBP-specific titers over time. The anti-DBP functional inhibition for each serum ranged from complete inhibition to no inhibition even for high-titer responders to the DBP, indicating that epitope specificity is important. Inhibitory immune human antibodies identified specific B-cell linear epitopes on the DBP (SalI) ligand domain that showed significant correlations with inhibitory responses. Affinity-purified naturally acquired antibodies on these epitopes inhibited the DBP erythrocyte binding function greatly, confirming the protective value of specific epitopes. These results represent an important advance in our understanding of part of blood-stage immunity to P. vivax and some of the specific targets for vaccine-elicited antibody protection.